Research on the Current Dilemma and Breakthrough Path of China's International Economic and Trade Rules for Elevation Standards - Shi, Jingwen; Zhou, Zejiong (International Journal of Global Economics and Management, 2024)
Currently, China has entered a stage of high-quality development. To deepen the new round of high-level opening up to the outside world, it is necessary to accelerate the construction of a domestic institutional system that is connected with international high standard economic and trade rules. This article takes high standard international economic and trade rules as the research object, focusing on the "Three Zero" rules, digital trade, competitive neutrality, intellectual property, government procurement, labor rules, etc. By sorting and summarizing the main rules of high standard economic and trade agreements such as CPTPP, USMCA, DEPA, etc., it analyzes the differences with domestic rule systems and the risks and challenges of China's integration. On this basis, this article proposes countermeasures and suggestions for international economic and trade rules based on elevation standards: firstly, steadily promote high-level opening up to the outside world and enhance the level of trade liberalization and facilitation; Secondly, accelerate the completion of domestic institutional reform and build an open economic system that is compatible with high standard economic and trade rules; Thirdly, actively promote the process of joining CPTPP and DEPA; Fourthly, actively participate in international economic and trade rule negotiations, and deeply participate in rule formulation and reshaping. The research findings of this article will provide useful references for China to further promote high-level opening-up and better participate in the formulation of international economic and trade rules.